Critical reflection of the application of 'reasonable chastisement' in South Africa : a case analysis of Freedom of Religion South Africa v Minister of Justice and Constitutional development - Hansungule, Michelo (University of Pretoria, 2020)
Mini Dissertation(LLM (Child Law))--University of Pretoria 2020.